Synthesis, Characterization and DNA-Binding Affinity of a New Zinc(II) Bis(5-methoxy-indol-3-yl)propane-1,3-dione Complex - Luca Scapinello; Guglielmo Vesco; Luca Nardo; Angelo Maspero; Federico Vavassori; Simona Galli; Andrea Penoni (MDPI AG, 2021)
The novel zinc(II) µ-oxo-bridged-dimeric complex [Zn2(µ-O)2(BMIP)2] (BMIP = 1,3-bis(5-methoxy-1-methyl-1H-indol-3-yl)propane-1,3-dione), 1, was synthetized and fully characterized. The spectral data indicate a zincoxane molecular structure, with the BMIP ligand coordinating in its neutral form via its oxygen atoms. Structural changes in 1 in dimethylsulfoxide (DMSO) were evidenced by means of spectroscopic techniques including infrared absorption and nuclear magnetic resonance, showing DMSO entrance in the coordination sphere of the metal ion. The resulting complex [Zn2(µ-O)2(BMIP)2(DMSO)], 2, readily reacts in the presence of N-methyl-imidazole (NMI), a liquid-phase nucleoside mimic, to form [Zn2(µ-O)2(BMIP)2(NMI)], 3, through DMSO displacement. The three complexes show high thermal stability, demonstrating that 1 has high affinity for hard nucleophiles. Finally, with the aim of probing the suitability of this system as model scaffold for new potential anticancer metallodrugs, the interactions of 1 with calf thymus DNA were investigated in vitro in pseudo-physiological environment through UV-Vis absorption and fluorescence emission spectroscopy, as well as time-resolved fluorescence studies. The latter analyses revealed that [Zn2(µ-O)2(BMIP)2(DMSO)] binds to DNA with high affinity upon DMSO displacement, opening new perspectives for the development of optimized drug substances.